2023
DOI: 10.21203/rs.3.rs-2555323/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular insight into the expression level of an immunosuppression gene, VTCN1, and its regulatory factors in breast cancer patients and non-cancerous samples with a higher level of IgE

Abstract: IgE levels increase in some cancer types due to treatment methods also autoimmune diseases can emerge and lead to worsening of the cancer. Finding a factor based on the reduction in IgE levels found in cancer can act as a determinant in providing the early diagnosis of the disease in individuals with high IgE levels in their blood. Accordingly, in the present study, the effort was made to select a gene associated with breast cancer and high IgE levels through available databases to evaluate the gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Another study revealed the possible regulatory role of LINC00520 on the ESR2 expression level in BC samples (Ezzati et al, 2022). Also, another study revealed that lncRNA NORAD regulates the expression level of VTCN1 in BC (Rezvani Sichani et al, 2023). Based on the study of Barani et al at 2022, LINC01215 could regulate the expression level of THBS2 in ECM receptor signaling pathway among gastric cancer patients (Barani et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…Another study revealed the possible regulatory role of LINC00520 on the ESR2 expression level in BC samples (Ezzati et al, 2022). Also, another study revealed that lncRNA NORAD regulates the expression level of VTCN1 in BC (Rezvani Sichani et al, 2023). Based on the study of Barani et al at 2022, LINC01215 could regulate the expression level of THBS2 in ECM receptor signaling pathway among gastric cancer patients (Barani et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…Our previous studies revealed the novel functions of lncRNAs in different cancer types. Based on the study of Rezvani Sichani et al, lncRNA NORAD regulates the expression level of VTCN1 in the BC samples (Rezvani et al, 2023).Barani et al revealed that lncRNA LINC01215 modulates ECM receptor signaling pathway through the regulation of THBS2 expression level in GC samples (Barani et al, 2022). LINC00520 also regulates the expression of ESR2 mRNA in BC samples as a potential diagnostic biomarker (Ezzati et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that certain lncRNAs have been identi ed as being dysregulated in peripheral blood mononuclear cells among individuals with MS, indicating their potential involvement in the pathogenesis of the disease (20,21). Our previous studies mentioned the potential biological roles of different lncRNAs in immune-related diseases, including different cancer types, including breast cancer (22)(23)(24)(25)(26), gastric cancer (27,28), and MS (29). Especially about MS, previous investigations mentioned novel regulatory lncRNAs with dysregulation in MS patients.…”
Section: Introductionmentioning
confidence: 99%